Maqashid al-Shariah, Social Dialogue, and Tourism Development in Lombok - SALAHUDDIN, Muh; ABDILLAH, Abdillah (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.13.8(64).13, 2022)
The study aims to describe the social dialogue in development of the tourism area in South Lombok. This study was strengthened by the concept of maqashid sharia as instrument of analysis to sharpen the theme studied. The Social dialogue was occurring when the local traditions (old values) meet a modernity (new values) and comes into the conflict. Indigenous people, local leader, government, investor are groups which are involved in the conflict. The conflict among groups was solved through social dialogue. Government bridged the interest of each group in dialogue process. In the case of this qualitative research, data were collected by interviews, observation, and documentation. Related references on the Sasak studies and tourism were used to sharpen analysis the collected data. The result of this study found that the social dialogue is carried out due the conflict generated by the development of the tourism area which covers issues of land ownership, distribution of power, economic distribution, and the shifting of traditional values. By the empowerment model approach, the government could communicate, facilitated, and guaranteed the needs and interest of each group in order to continue the development of tourism area.